Standardization of pediatric cardiovascular anomaly anatomy reconstructions - Alzaeim, Mohamad Humam; Köse, Kevser Banu; Pişkin, Şenol; Basha, Wael Shamsi; Güngören, Fatma Zeynep; Şahin, Ömer Faruk; Femilda, Josephin (My University, 2024)
In the realm of congenital cardiovascular diseases, the understanding, modeling, and visualization of such diseases as they develop during the neonatal growth period continues to be a challenge despite the current technological advancements. Moreover, such diseases as vascular abnormalities pose further risks due to their implications for a proper standardized method for three-dimensional visualization for planning and growth monitoring. This study uses imaging and computational techniques to create multiple models that relate the diseases as they progress from the initial phase toward the late growth stage for newborns’ cardiovascular systems. Three-dimensional modeling of patients would be created from patient-specific scans coupled with image processing algorithms. This study also aims to use the working principles of already existing tools for diagnosing aortic & brain aneurysms and pulmonary hypertension for cardiovascular development. To comprehensively understand such diseases and how their physical morphology may be standardized.
Keywords: Cardiovascular System; Congenital Heart Diseases; Disease Modeling; Geometric Visualization; Three-Dimensional Modelling